Anstöße zur linguistischen textanalyse - Lysetska, Nataliya Hryhorivna; Лисецька, Наталія Григорівна (My University, 2017)
Abstract. The paper proposes a scheme of comprehensive text analysis that can be a model as one of the possible options for working with students of IV and V courses of study on specialty “German Language and Literature” as the main or second foreign language and their preparation for exams. The basic concepts and categories of linguistic analysis from the point of view of such disciplines as German language stylistics, text linguistics, cognitive linguistics and literature of Germany as well as the steps of work on literary text are given. Special attention is paid to consideration the basic theoretical principles of linguistic analysis and its application in practice. Taking that into consideration, an analysis of an excerpt from “Effi Briest” novel by Theodor Fontane, a famous German writer of the poetic realism era. The selected text passage is being analyzed in accordance with the scheme proposed by the author that provides for the definition of the genre and functional style based on certain criteria, characteristics of the era and the writer’s course of life. An important element in bells lettres is the means of expressing the author’s position (auktorial narrator in the form of a third party (auktorialer Erzähler), the narrator in the form of “I”(personaler Erzähler) ‒ with consideration of possible genre variations) and time-spatial relationship that manifests itself in two ways ‒ real-time artistic reality of the characters and time that is necessary for the recipient to understand this reality. Semantic integrity of the text is reproduced on the basis of cohesive and coherent communication means. To cohesive (surface) ones belongs a number of lexical (different types of repetitions, hyper-hyponymy, synonyms, antonyms, etc.), stylistic (functional and stylistic belonging, figurative comparisons, parallelisms, periphrases, etc.) and grammatical(substitution, recurrence, pro-forms, ellipses, hypotaxis, parataxis etc.) means. Under coherent ones we understand internal semantic relations in the text. They are always implicit, imaginary, unspoken,associative. The role of conceptual links for coherence of the text is shown.
Keywords: Linguistik; Textanalyse; stylistic devices; linguistic analysis of the text; conceptual ties; cohesion; coherence; implicit meanings; concept; stylistics